2017
DOI: 10.1002/tesq.393
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Theoretical Perspectives on Task‐Based Classroom Realities

Abstract: Tasks are viewed as a principled foundation for classroom teaching, social interaction, and language development. This special issue sheds new light on how task-based classroom practices are supported by a diverse range of principles. This introduction describes current trends in classroom practice and pedagogic research in relation to task-based language teaching (TBLT), offering a rationale for revisiting the TESOL profession's understandings of the uses of tasks in language classrooms. It then summarizes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Decades of research on task-based language teaching and learning (TBLT) have demonstrated that tasks may encourage second/foreign language (L2) development by providing conditions for cognitive processes and social interactions that facilitate L2 acquisition (e.g., Long, 2015; Robinson, 2011; Skehan, 2014; for alternative, noncognitive viewpoints on TBLT, see Jackson & Burch, 2017). Specifically, manipulating task features has been shown to draw learners’ attention to target forms within meaning-based interaction; to encourage automatization and fluency of target structures; and to promote use of more accurate, varied, and/or complex forms.…”
mentioning
confidence: 99%
“…Decades of research on task-based language teaching and learning (TBLT) have demonstrated that tasks may encourage second/foreign language (L2) development by providing conditions for cognitive processes and social interactions that facilitate L2 acquisition (e.g., Long, 2015; Robinson, 2011; Skehan, 2014; for alternative, noncognitive viewpoints on TBLT, see Jackson & Burch, 2017). Specifically, manipulating task features has been shown to draw learners’ attention to target forms within meaning-based interaction; to encourage automatization and fluency of target structures; and to promote use of more accurate, varied, and/or complex forms.…”
mentioning
confidence: 99%
“…Another potential avenue to consider is that of task‐based language teaching (TBLT). Though there is still a level of vagueness in how to define TBLT in the language teaching community, in its most pure sense, TBLT promotes language learning in relation to real‐world contexts (Jackson & Burch, ; Long, ). Specifically, learners are required to complete interactive tasks, which increase the potential for communicative breakdown.…”
Section: Resultsmentioning
confidence: 99%
“…"What is a task?" seems to be a simple question, but there have been a variety of definitions and classifications (Ellis & Shintani, 2014;Jackson & Burth, 2017;Richards & Rodgers, 2014;Van den Branden, 2006). Among the various definitions, Ellis (2003) and Ellis and Shintani (2014) suggested four criteria for defining a "task.…”
Section: Definition Of Tasksmentioning
confidence: 99%